GOLDBACH CONJECTURE: METHOD TO DETERMINE PRIME PAIRS - Sousa, José Emanuel; Garrão, Ana Paula; Dias, Margarida Raposo (European Scientific Journal, ESJ, 2015)
Being the Goldbach Conjecture considered the most famous conjecture unsolved, concerning prime numbers, this paper is dedicated to prime numbers, seeking to create a method to determine prime pairs for a given even number. This method, described in the paper, allows to determine a Goldbach partition for an even number, sometimes even all, in a practical and effective way, without using complex algorithms.